Leaf Phosphate Status, Photosynthesis, and Carbon Partitioning in Sugar Beet (IV. Changes with Time Following Increased Supply of Phosphate to Low-Phosphate Plants) - Rao, Idupulapati M.; Terry, Norman (American Society of Plant Biologists, 1995)
Changes in photosynthesis, carbon partitioning, and growth following resupply of orthophosphate (Pi) to moderately P-deficient plants (low-P) were determined for sugar beets (Beta vulgaris L. cv F58–554H1) cultured hydroponically in growth chambers. One set of plants was supplied with 1.0 mM Pi in half-strength Hoagland solution (control plants), and a second set (low-P plants) was supplied with 0.05 mM Pi. At the end of 2 weeks, the low-P plants were resupplied with 1.0 mM Pi. Low-P plants rapidly accumulated large amounts of Pi, and the photosynthesis rate increased to control values within 4 to 6 h. The rate of photosynthesis appeared to be controlled by ribulose-1,5-bisphosphate (RuBP); low P reduced photosynthesis and RuBP levels, and P resupply increased photosynthesis and RuBP in a manner parallel with time. Low-P treatment reduced adenylate levels substantially but not nicotinamide nucleotides; adenylate levels recovered to control values over 3 to 6 h. With low P, more photosynthate is allocated to non-P carbon compounds (e.g. starch, sucrose) than to sugar phosphates. When P is resupplied, sugar phosphates increase as starch and sucrose pools decrease; this increase in leaf (chloroplast) sugar phosphates was most likely responsible for the increases in RuBP and photosynthesis and may have increased adenylate levels (through enhanced levels of ribose-5-phosphate).